Task of work distribution for the development of project solutions it-company - Sibilov, V. O.; Snitko, A. O. (ХНУРЕ, 2023)
The Hungarian method is one of the most in-demand mathematical method required nowadays. It helps to solve the distribution task of human resources and find the most optimal result of the assignment task. The development of this method includes all its strengths and weaknesses that it can provide in order to find the smartest way of solving the assignment task and can be used by IT companies